Digitalizing multidisciplinary pulmonary rehabilitation in COPD with a smartphone application: an international observational pilot study - Frank Rassouli; David Boutellier; Jonas Duss; Stephan Gerhard Huber; Martin Brutsche (2018)
Concerning COPD, pulmonary rehabilitation (PR) has a positive effect on disease progression and mortality, is cost-effective, and is a part of recommendations of international guidelines. Only a minority of patients profit from conventional PR due to a lack of resources, physicians' guideline adherence, or patients' motivation. Novel digital therapies like Kaia COPD, a smartphone application that digitizes PR in COPD, are promising solutions to fill this void.Kaia COPD provides a digital version of PR and is certified as a class-I medical device in the European Union. We investigated anonymized data from users of the Kaia COPD app on in-app retention and the change in health-related quality of life (COPD assessment test and Chronic Respiratory Disease Questionnaire [CRQ]) during a period of 20 exercise days with the app.Of 349 app downloads, 56 users fulfilled inclusion criteria and 34 (61%) had finished day 20 at the time of analysis and were included. Users took 33±11 days to complete the 20-day core program. Users finishing the program reduced their COPD assessment test scores (mean 2.5 units from 21.6±7.7 to 19.1±8.4 units, P=0.008). In finishers, there was a statistically significant effect above the minimum clinically important threshold of the CRQ score on the domains of fatigue, mastery, and emotional function. There was a statistically significant but not clinically relevant effect on the domain of dyspnea of CRQ.Digitalizing PR with a smartphone app is feasible and accepted by selected patients. The app leads to short-term improvement of health-related quality of life in patients completing a 20-day core program. Due to its observational character, this study has several methodological limitations and was intended to show the feasibility and to extrapolate effect sizes for planned prospective randomized-controlled trials to confirm these findings.